AUDIOVISUAL MEDIA AS ONE OF THE HEALTH EDUCATION MEDIA THAT CAN AFFECT ADOLESCENT PERSONAL BEHAVIORS IN THE MANAGEMENT OF LEUKORHEA - Yanita Trisetiyaningsih; Ida Nursanti (Universitas Respati Yogyakarta, 2021)
At puberty, young women will experience an increase in the hormone estrogen, allowing adolescents to experience vaginal discharge. Leucorrhoea can be caused due to wrong habits in doing personal hygiene. In Indonesia 2013 there were 237,641,326 cases of adolescents experienced vaginal discharge (75%) Based on statistical data in Indonesia 2008, of 43.3 million adolescents aged 15-24 years of unhealthy behavior which is one of the causes of leucorrhoea According to static data in the Special Region of Yogyakarta in 2009 the number of teenagers 2.9 million people aged 15-24 years 68% experience vaginal discharge. The objective studyd is knowing the effect of health education with audiovisual methods on knowledge, attitudes, and personal hygiene behavior in handling vaginal discharge. This research is conducted at SMP Negeri 1 Gamping for class XIII and IX. Data collection begins with conducting a pretest, providing health education with audiovisual methods, and posttest. The data obtained will be performed univariate analysis and bivariate analysis using the Wilcoxon Signed Rank Test. The average score of the level of knowledge in the pretest handling was 85.3 and the posttest was 86.7. The average score of the pretest attitude was 80.7 and the posttest was 80.8. The average score of the pretest behavior was 73.4 and the posttest was 76.3. Health education using audiovisual does not affect the level of knowledge and attitudes of adolescents in handling vaginal discharge, but does affect adolescent behavior. Keywords: Adolescent; Vaginal Discharge